On Models of Syllable Division - Murray, Robert (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1989)
AbstractPicard (1983, 1987b) claims that his model of syllable division predicts the placement of a syllable boundary in any given sequence of segments for a particular language. In this article, I show that this model is inadequate in three ways; a) it does not take into consideration language specific differences in syllable structure, particularly of sequences of the type VPLV and VPGV (where P = plosive, L = liquid, and G = glide) which can be syllabified V$PLV/V$PGV or VP$LV/VP$GV depending on language specific factors, b) it fails to predict the correct placement of syllable boundaries for certain languages (e.g. Huichol), and c) it fails to take into consideration the existence of ambisyllabic segments.